State of knowledge: River health in the Salween- Chinese - Johnston, Robyn M.; McCartney, Matthew P.; Liu, Shaoyu; Ketelsen, Tarek; Taylor, Luke; Vinh, Mai Ky; Mehm, Ko Ko Gyi; Aung, Theiant; Ma Ma Gyi, Khin (CGIAR Research Program on Water, Land and Ecosystems, 2017)
This State of Knowledge paper reviews what is known about river health in the Salween Basin, including both the current state and uses of the river and its catchment, and issues likely to drive change in the near future. This report is in Chinese language.